Death's door ebook - Benn, James R. (Billy Boyle World War II Mystery, 2012)
In this seventh installment of James R. Benn’s hit WWII-era mystery series, Lieutenant Billy Boyle goes undercover in the Vatican .   Lieutenant Billy Boyle could have used a rest after his last case, but when his girlfriend, Diana Seaton, a British spy, goes missing in the Vatican, where she was working undercover, he insists on being assigned to a murder investigation there so he can try to help her.   An American monsignor is found murdered at the foot of Death's Door, one of the five entrances to Saint Peter's Basilica. Wild Bill Donovan, head of the OSS, wants the killing investigated. The fact that the Vatican is neutral territory in German-occupied Rome is only one of the obstacles Billy must overcome. First is a harrowing journey, smuggled into Rome while avoiding the Gestapo and Allied bombs. Then he must navigate Vatican politics and personalities—some are pro-Allied, others pro-Nazi, and the rest steadfastly neutral—to learn the truth about the murdered monsignor. But that's not his only concern; just a short walk from the Vatican border is the infamous Regina Coeli prison, where Diana is being held. Can he dare a rescue, or will a failed attempt alert the Germans to his mission and risk an open violation of Vatican neutrality?